Pemanfaatan Perpustakaan Sebagai Sumber Belajar Siswa di MTs Ma’arif Sukoharjo - Siti Lailiyah (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2024)
This research aims to describe the library as a learning resource at MTs Ma’arif Sukoharjo. This type of research uses a qualitative descriptive method, namely research that is intended to understand the phenomenon of what is experienced by research subjects, producing descriptive data in the form of written or spoken words from people and observed behavior to find out how students use the library as a learning resource. . Data sources for data collection techniques are observation, interviews and documentation. The data sources in this research consist of two types, namely primary and secondary. The results of this research show that: (1) General description of Takhassus Al-Qur'an High School in Mojotengah Wonosobo (2). Condition of the school library at Takhassuss Al-Quran High School in Mojotengah, Wonosobo.